An Optimal Final Inventory Model - Hadley, G.; Whitin, T. M. (Management Science, 1961)
A model is developed which allows the determination of the optimal inventory level for an item at any time if no additional procurements are to be made. It is assumed that the item has a known date of obsolescence and that the demand is Poisson distributed with a fixed mean over the useful life of the tem. The model constitutes an extension of other life-of-type models in that both costs which are incurred at a fixed point in time (liquidation losses) and other costs which are a function of time (carrying charges and stock-out costs) are included. In many operational situations both of these types of costs are relevant.